1999
DOI: 10.1046/j.1525-1470.1999.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Generalized Varicella Zoster in the Setting of Preexisting Generalized Erythema

Abstract: We report a 5-year-old girl who initially had generalized erythema from scarlet fever. Four days later she developed sheets of monomorphous vesicles in the areas of erythema. A Tzanck smear of a vesicle base showed multinucleated giant cells, and viral culture grew varicella zoster virus, confirming a clinical diagnosis of varicella. This case illustrates that, with a background of preexisting erythema, varicella may present in an atypical manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…A very characteristic feature of varicella is the finding of lesions in all stages of development at one time in the same area. The diagnosis of varicella is usually made from this characteristic clinical presentation and may be confirmed by the finding of multinucleated giant cells on a Tzanck smear of cells scraped from the base of an early vesicle (9). The diagnosis of varicella in our patient was made from this characteristic clinical presentation and confirmed by a high VZV‐IgM titer in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…A very characteristic feature of varicella is the finding of lesions in all stages of development at one time in the same area. The diagnosis of varicella is usually made from this characteristic clinical presentation and may be confirmed by the finding of multinucleated giant cells on a Tzanck smear of cells scraped from the base of an early vesicle (9). The diagnosis of varicella in our patient was made from this characteristic clinical presentation and confirmed by a high VZV‐IgM titer in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying dermatoses may modify the exanthem. Egan et al 5 . reported an acute generalized varicella with a pre‐existing scarlet fever generalized erythema.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical varicella has been associated with immunosuppression, 2 skin injury, 3 sun exposure 4 and pre‐existing cutaneous disease 5 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical diagnosis of primary varicella was supported by history of recent exposure to varicella and absence of prior varicella in all cases, by a Tzanck smear in 21 cases and by a positive test for varicella zoster virus in 7 cases. Twentyfour cases were photo-localised [8][9][10][11][12][13][14][15][16][17][18]20,21,23,24,28,30,31,33,38,41,43 and 35 6,7,14,16,19,21,22,[25][26][27]29,30,32,[34][35][36][37]40,42 skin inflammation associated. Females (79%) predominated in the cases with photo-localised varicella, males (57%) in the group with skin inflammation-associated varicella (p < 0.01).…”
Section: Clinical Datamentioning
confidence: 99%
“…The study flowchart is shown in Figure 1. For the final analysis, we retained 38 communications published between 1927 and 2021 in English ( N = 33), French ( N = 3) or Spanish ( N = 2) 6–43 …”
Section: Synthesismentioning
confidence: 99%